Kondisi Stres Akademik Siswa Selama Pembelajaran Daring - Saskia Okti Granita (Jurnal Halaqah, 2021)
The study aimed to see an overview of academic stress levels and to identify differences in student academic stress based on gender and major during the online learning process. The quantitative approach of descriptive analysis and non-parametric Mann-Whitney test was used in this study. The population consisted of 990 students of SMA N 1 Linggo Sari Baganti. The sample in this study amounted to 113 students obtained using a simple random sampling technique. The results showed that 67.3% of students had moderate academic stress. Asymp.Sig. (2-tailed) based on gender 0.248> 0.05 and Asymp.Sig. (2-tailed) based on the direction 0.138> 0.05. It can be concluded that overall students of SMA N 1 Linggo Sari Baganti who take online learning are in the medium category of academic stress and there is no significant difference in academic stress based on gender or major.